The Use of an Electroactive Marker as a SERS Label in an E-melting Mutation Discrimination Assay - Mahajan, S; Richardson, J; Ben Gaied, N; Zhao, Z; Brown, T; Bartlett, P (2009)
In this paper we describe the first example of the use of an electroactive label as a SERS marker for detecting and quantifying target oligonucleotides and distinguishing mutations using a combination of voltammetry and electrochemically induced melting (E-melting). The experiments were carried out on sphere segment void substrates selected to show strong surface enhancement for SERS at 633 nm. DNA analysis was carried out for CFTR sequences using synthetic 22-mer oligonucleotides labelled with a modified anthraquinone at the 3'-end. Discrimination between the wild type, 1653C/T (point mutation) and DF508 (triple deletion) is demonstrated. © 2009 Wiley-VCH Verlag GmbH and Co. KGaA, Weinheim.